School Superintendents as Translators of Policy from the National to the Municipal Level: Emerging Discourse About an Evidence-Based Practice - Bjursell, Cecilia; Sjödahl, Charlotte; Hedegaard, Joel (Scandinavian Journal of Public Administration, 2023)
Policy discourses focus on (and set limits to) what is considered acceptable to say and to do. Within a discourse, a dominant idea can influence how the discourse unfolds. The present study examines the dominant idea that education should be an evidence-based practice. We explore how this dominant idea at the national level is translated into local practice by school superintendents at municipal education departments in a Swedish context. Sixty-five of Sweden’s 290 municipalities were chosen for this study based on their geographical location and size. We found 16 documents from nine authorities that explicitly mentioned evidence-based practice. A discourse analysis of these documents identified six themes that may indicate how school superintendents interpret and translate the dominant idea. The discourses are evidence-based practice in terms of (i) ‘mirroring’, (ii) ‘professional competence’, (iii) ‘collaboration’, (iv) ‘literature review’, (v) ‘method’, and (vi) ‘quality work’. Thus, there are a number of different ways in which the national policy is translated at the municipal level. What we observe in the discourses, however, expresses provisional attempts at defining evidence-based practice, thereby suggesting that, at the local level, education management teams are prepared to accommodate ideas from alternative areas instead of relying on and developing methods and ways of working that (historically) have been used in education. A critical insight for practice is that we should examine the grey areas between research and policy; specifically, where policy materials imitate research in an attempt to influence practice under the disguise of ‘evidence’.